Electrodeposition of One-Dimensional Nanostructures: Environmentally Friendly Method - Sousa Neto, Vicente de Oliveira; Saraiva, Gilberto Dantas; de Castro, A. J. Ramiro; Cavalcante Freire, Paulo de Tarso; do Nascimento, Ronaldo Ferreira (Journal of Composites and Biodegradable Polymers, 2022)
During the past decade, nanotechnology has become an active field of research because of its huge potential for a variety of applications. When the size of many established, well-studied materials is reduced to the nanoscale, radically improved or new surprising properties often emerge. There are mainly four types of nanostructures: zero, one, two and three dimensional structures. Among them, one-dimensional (1D) nanostructures have been the focus of quite extensive studies worldwide, partially because of their unique physical and chemical properties. Compared to the other three dimensional structures, the first characteristic of 1D nanostructure is its smaller dimension structure and high aspect ratio, which could efficiently transport electrical carriers along one controllable direction; as a consequence they are highly suitable for moving charges in integrated nanoscale systems. The second characteristic of 1D nanostructure is its device function, which can be exploited as device elements in many kinds of nanodevices. Indeed it is important to note that superior physical properties including superconductivity, enhanced magnetic coercivity and the unusual magnetic state of some 1D nanostructures have been theoretically predicted and some of them have already been confirmed by experiments. In order to attain the potential offered by 1D nanostructures, one of the most important issues is how to synthesize 1D nanostructures in large quantities with a convenient method. Many synthetic strategies, such as solution or vapor-phase approaches, template-directed methods, electrospinning techniques, solvothermal syntheses, self-assembly methods, etc., have been developed to fabricate different classes of 1D nanostructured materials, including metals, semiconductors, functional oxides, structural ceramics, polymers and composites. All the methods can be divided into two categories: those carried out in a gas phase (i.e., “dry processes”) and those carried out in a liquid phase (i.e., “wet processes”). The dry processes include, for example, techniques such as chemical vapor deposition (CVD), physical vapor deposition (PVD), pulse laser deposition (PLD), metal-organic chemical vapor deposition (MOCVD), and molecular beam epitaxy (MBE). In general, these gas phase processes require expensive and specialized equipments. The wet processes include sol-gel method, hydrothermal method, chemical bath deposition (CBD) and electrodeposition. Among the above mentioned methods, electrodeposition has many advantages such as low cost, environmentally friendly, high growth rate at relatively low temperatures and easier control of shape and size. Generally, there are two strategies to produce the 1D nanostructures through the electrochemical process. They are the template-assisted electrodeposition, and the template-free electrodeposition. In this chapter, we will approach the recent progress and offer some prospects of future directions in electrodeposition of 1D nanostructures. Electrodeposition is a simple and flexible method for the synthesis of one-dimensional (1D) nanostructures and has attracted great attention in recent years.